Augustine and Phil. 3, 3-16: One bible fragment, several exegetical approaches - Eelen, Alicia (2011)
The present article provides a comparative study of Augustine’s sermones ad populum 169 and 170. Both sermons treat more or less the same bible fragment, namely verses 3 (or 6)-16 of the third chapter of Paul’s letter to the Philippians. The argumentative structure of the two sermons will be examined on the basis of mainly content-related indications and certain explicit markers of structure. It will become clear that s. 169’s structure is that of a line-by-line commentary on these bible verses, while the structure of s. 170 resembles that of a quaestio. By comparing these different structures, it will become clear that the sermons treat the bible fragment differently. This divergence will be explained by the presence of a different type of audience (namely, people whom Augustine believed to possess great spiritual quality for s. 169, a heterogeneous public for s. 170).